Efeitos da exposição a estímulos aversivos imediatos sobre a catalepsia induzida por haloperidol: possível modelo animal para cinesia paradóxica - Waku, Isabelle (Universidade Federal de São Carlos, 2021)
Haloperidol – a dopaminergic D2 antagonist – acts on the nigrostriatal pathway inducing catalepsy, a state of immobility similar to the bradykinesia of Parkinsons disease (PD). Therefore, haloperidol-induced catalepsy in rodents is used as a model for the study of PD motor impairments. The bradykinesia in PD appears to be related to the patients emotional state, for example, immobile patients capable of performing sudden movements when exposed to aversive stimuli, a phenomenon known as paradoxical kinesia. Thus, it is of great interest to study the relationship between catalepsy and emotional states in rats. In this sense, in a previous study, we started to assess the effects of the presentation of aversive stimuli at the exact moment of exposure of rats to the catalepsy test, with results pointing to a possible attenuation of the cataleptic state. The present study continued this evaluation. In the first stage, we conducted a study of systematic literature review in order to identify publications that report the use of haloperidol-induced catalepsy as an animal model for parkinsonism, and to explore the methodological characteristics and the main issues addressed in these studies. In the second stage, in an experimental study, we investigated the effects of unconditioned and conditioned aversive stimuli on haloperidol-induced catalepsy. For this, 162 male Wistar rats received intraperitoneal administration of saline or haloperidol (1 or 2 mg/kg) and were evaluated in the catalepsy test. Three experiments were carried out in order to: I. Assess the intensity of the cataleptic state induced by the different doses of haloperidol over time; II.Evaluate the effects of three types of unconditioned aversive stimuli - 75 dB noise (1 and 20 s of duration), 100 lux light (1 and 20 s), or 0.6 mA footshocks (1 s) - on the catalepsy; III. Evaluate the effects of light and sound conditioned aversive stimuli (previously paired with shocks) on catalepsy. Catalepsy was the main effect produced by haloperidol and observed in the two doses used. Exposure to unconditioned sound or light stimuli did not cause significant effects on catalepsy compared to the group itself before receiving the stimulus (baseline) or compared to the non-stimulated group. On the other hand, exposure to shock caused a significant reduction in the latency to remove the paws during the catalepsy test compared to the group itself before receiving the stimulus. Exposure to fear conditioned using sound did not alter catalepsy. Exposure to fear conditioned using light significantly reduced catalepsy, both for the group that received light and shocks in a paired and non-paired manner during training. The results suggest that the effect on haloperidol-induced catalepsy is dependent on the modality/intensity of the aversive stimuli used. Exposure, during the catalepsy test, to shocks or lights previously associated with shocks is capable of disrupting the cataleptic state, pointing to a model with face validity for the study of paradoxical kinesia.
Effects of exposure to immediate aversive stimuli on haloperidol-induced catalepsy: possible animal model for paradoxical kinesia
Keywords: Bradicinesia; Doença de Parkinson; Estado emocional; Dopamina; Antagonista D2; Ratos; Bradykinesia; Parkinson's disease; Emotional state; Dopamine; D2 antagonist; Rats; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::PSICOBIOLOGIA